A putative novel type of tight adherence (tad) like gene cluster of Pseudomonas Chlororaphis PCL1606 exhibits a crucial role in avocado roots colonization, fostering its biological control activity - Ruiz-Muñoz, Blanca; Rodríguez-García, María; Heredia Ponce, Zaira María; Tienda, Sandra; Villar-Moreno, Rafael; Arrebola-Díez, Eva María; De-Vicente-Moreno, Antonio; Cazorla-López, Francisco Manuel; Gutiérrez Barranquero, José Antonio (Springer Nature, 2025)
Aims Pseudomonas chlororaphis PCL1606 (PcPCL1606), displays strong antagonistic and biological control abilities against several soil-borne fungal pathogens mainly due to the production of the antifungal molecule 2-hexyl, 5-propyl resorcinol (HPR). HPR governs other beneficial phenotypes, suggesting its additional regulatory activity. Published transcriptomic data identifying HPR-regulated genes involved in the interaction of PcPCL1606 with the avocado rhizosphere were used as a target database to identify putative genes involved in avocado roots colonization. Methods The induction of several consecutive genes that showed homology with genes encoding a putative type IV Flp/Tad (tight adherence) pilus but with a few differences from the Tad type A and B was observed. To study the role of this tad-like gene cluster in the biology of PcPCL1606, a chromosomal deletion mutant was constructed. The molecular characterization of the tad-like gene cluster and different in vitro and in vivo phenotypes related to colonization were addressed in the mutant strain respect to PcPCL1606. Results The tad-like gene cluster was composed of five independent transcriptional units. Furthermore, the tad-like deletion mutant was impaired in early attachment, early biofilm formation, bacterial autoggregation and in root competitiveness in avocado plants and biocontrol activity against R. necatrix. Conclusions These results expand our understanding about the role of HPR as a putative signalling molecule. This study revealed the importance of a putative novel type of a Tad system of PcPCL1606 in the avocado roots colonization, confirming that initial attachment to roots is a fundamental mechanism for the PcPCL1606 rhizospheric performance.
Keywords: Rizobacterias; Agentes antifúngicos; Pseudomonas chlororaphis PCL1606; Avocado roots colonization; HPR signaling network; Tad-like pilus